RETRACTED: GROUND GLASS OPACITIES IN LUNG CANCER PATIENTS POSITIVE FOR COVID-19 - TARIQ, F; IRFAN, A; SATTAR, A; ASLAM, MA; SHEIKH, R (Biological and Clinical Sciences Research Journal, 2023)
Retraction Notice: This paper has been retracted from the journal after receipt of written complains from IRB & Ethical Committee, Shifa International Hospital Ltd. Islamabad, Pakistan. This journal is determined to promote integrity in research publication. This retraction is in spirit of the same. After formal procedures editor(s) and publisher have retracted this paper on 21th February-2023. Related policy is available here: http://bcsrj.com/ojs/index.php/bcsrj/AWP